Edukasi Tanda-Tanda Bahaya Dalam Kehamilan Pada Ibu Hamil Desa Bangun Rejo Kecamatan Tanjung Morawa Kabupaten Deli Serdang - Marta Armita Silaban; Damayanty S; Erin Padila Siregar; Ika Damayanti (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2022)
A high-risk pregnancy is a pregnancy that is likely to cause harm or complications to both the mother and the fetus she contains during pregnancy, childbirth or the puerperium when compared to normal pregnancies and childbirth. Method: educating pregnant women about the danger signs of pregnancy by using leaflets. Results: Participants in this activity were 25 pregnant women in Sumber Rejo Village. In its implementation, the target is explained about the correct danger signs of pregnancy, benefits, how to detect danger signs of pregnancy. Next, explain when pregnant women should immediately check their pregnancy if they feel complaints about their pregnancy. Conclusion: counseling-based community service activities are carried out. Service activities carried out for 3 months. The results of this Community Service regarding danger signs of pregnancy. This community service has been carried out from August to September 2022 to be precise for 3 months.